The Economics of Environmental Health: Bibliometric Insights into Cost-Benefit and Public Policy Approaches - Judijanto, Loso (Westscience Press, 2025)
Environmental health economics has emerged as a necessary interdisciplinary field of research that addresses the complex interaction among environment quality, public health, and economic policy. This study conducts a bibliometric analysis at the world level to map the intellectual landscape of the field, with a particular focus on cost-benefit analysis and public policy measures. Based on the Scopus database between 2000 and 2025 and VOSviewer for visual network analysis, the study identifies the top authors, institutions, countries, and research topics that have been prominent in the field. The findings of the research validate that